Angiogenic factors in pregnancies of women with antiphospholipid syndrome and systemic lupus erythematosus. (June 2018) - Mayer-Pickel, Karoline; Stern, Christina; Eberhard, Katharina; Lang, Uwe; Obermayer-Pietsch, Barbara; Cervar-Zivkovic, Mila
Highlights: The antiphospholipid syndrome and systemic lupus erythematosus have an increased risk of developing especially preeclampsia in pregnancy. Measurement of sFlt-1, PGlF and endoglin starting at early gestation optimizes the obstetric management and might improve the obstetric outcome. Regular measurements of sFlt-1 and PlGF especially as a matter of routine should be an essential part of obstetric management. Abstract: Objectives: An imbalance of angiogenic placental factors such as endoglin, soluble fms-like tyrosine kinase 1(sFlt-1) and placental growth factor (PlGF) has been implicated in the pathophysiology of preeclampsia. This study aimed to evaluate serum levels of sFlt-1, PlGF and endoglin in women with primary and secondary antiphospholipid Syndrome (APS) and systemic lupus erythematosus (SLE) longitudinally through pregnancy. Material and Methods: Serum levels of sFlt-1, PlGF and endoglin were measured prospectively at 4-week intervals (from gestational weeks 12–36) in 17 women with primary APS (PAPS), 18 women with secondary APS (SAPS), and 23 women with SLE. Results: 6/17 (35%) of women with PAPS, 3/18 (17%) of women with SAPS, and 2/23 (9%) of women with SLE developed early-onset preeclampsia. Women who developed preeclampsia had significantly higher mean sFlt-1 and endoglin levels, higher sFlt-1/PlGF ratios, and lower mean PlGF-levels than women who did not. These changes became statistically significant at 12 weeks for sFlt-1, PlGF and endoglin. Discussion: Endoglin, sFlt-1 and PlGF are potential early screening parameters for the development of preeclampsia in pregnant women with autoimmune diseases like APS and SLE.